Macroeconomic variables as determinant of economic growth in Nigeria. A dynamic generalized method of moment approach - Kutu, Augustine Adebayo; Ohonba, Abieyuwa (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of macroeconomic variables on economic growth in Nigeria. Employing a time series data from 1986Q1 – 2022Q4 and GMM as well as dynamic GMM models, the results show a significant contribution of all the macroeconomic variables to economic growth. Also, the short and long run equilibrium relationship were established among the variables. It was observed that the variables are stationary at different levels of integration leading to the fitted generalized method of moment models. Thus, it was revealed that previous economic growth, internal debt, interest rate, exchange rate and trade openness significantly contributed to economic growth to the turn of 76.21%, 3.79%, 7.01%, 4.45% and 40.12% respectively. It was further revealed that external debt led to a 0.3% decline in economic growth. As a policy implication and recommendation, both internal and external borrowing must be properly monitored and channeled to productive investment as well as the needed infrastructure that would improve economic growth. An enabling environment should be provided for foreign investors to attract better investment that could enhance economic growth. Trade openness barriers must be removed to engender free entry and exist of goods and services required to grow the economy.